Trade-offs between nutrient export, greenhouse gas balance and financial performance in continuous cover and rotation forestry in drained peatlands in northern Finland - Ahtikoski, Anssi; Repola, Jaakko; Hökkä, Hannu; Sarkkola, Sakari; Ojanen, Paavo; Haikarainen, Soili; Stenberg, Leena; Juutinen, Artti (The International Mire Conservation Group (IMCG), 2025)
Peer reviewed